La propension à l’interdisciplinarité des étudiants en situation d’innovation - Thomas Houy; Yohan Attal; Yohann Melamed (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
The article provides insight on students’ strategies when they have to work in an interdisciplinary group working on an innovative project. We show that students are willing to work in a team made up of students studying in other disciplines. This inclination for interdisciplinary approaches depends both on the type of students and the institutions. The outcomes are the result of processing data obtained through the Studyka platform. This online platform provides opportunities for the students to work together, whatever their skills and institution, and to deal with a challenge in innovation.